Ten Common Misses in PBIS Implementation. (April 2021) - Tyre, Ashli D.; Feuerborn, Laura L.
The success of positive behavioral interventions and supports (PBIS) frameworks relies upon educators supporting and implementing PBIS plans. However, common staff-level perceptions exist that may interfere with successful implementation, which we refer to as misses. In this article, three types of misses representing common sets of staff concerns for PBIS implementation are discussed: misunderstandings, misapplications, and misalignments of educator philosophies. We discuss common misses, unpack them from the perspective of implementers, and provide suggestions for supporting staff. Common misses in PBIS can be prevented and successfully addressed when they occur through staff engagement, professional development, and implementation support.